Agent programming using defeasible argumentation for knowledgerepresentation and reasoning - Gottifredi, Sebastián (2007)
In this work two declarative approaches based on the BDI theory are studied, an agent programming language 3APL and an agent architecture that uses defeasible argumentation for knowledge representation and reasoning. Based on that study and considering that in 3APL the knowledge representation language is not fixed, we will propose 3APL-DeLP where the agent knowledge is represented by a DeLP-program and the agent may reason with a defeasible argumentation formalism.